(untitled) (Jurnal Teknologi Industri Pertanian, 2018)
Rumah Kedelai Grobogan (RKG) focuses on the production and dissemination of local soybean Grobogan varieties. One of its business units, Rumah Tempe, produces hygienic tempe from soybean Grobogan varieties. It has good prospect and is expected to be the driver of the development of RKG. The development of Rumah Tempe is expected to increase the use of the Grobogan varieties and improve RKG performance. This research aims to determine an appropriate strategy for Rumah Tempe. This research focuses on four stages: (1) identifying factors influencing Rumah Tempe’s business development, (2) determining and selecting criteria of business development, (3) determining alternatives for business development, (4) selecting the most preferred strategy for Rumah Tempe’s business development. Analytical Hierarchy Process (AHP) was conducted to prioritize the preferred strategy. The results show the criteria were weighted as follows: (1) New product development (0.1022), (2) Product quality (0.2747), (3) Continuity product availability (0.2938) and (4) Customer satisfaction (0.3293). Customer satisfaction is the most prioritized criteria in Rumah Tempe’s business development. Alternative strategy isclassified into four types: prospector strategy, defender strategy, analyzer strategy, and reactor strategy. The result of the assessment shows that defender strategy is the most preferred prioritized strategy for Rumah Tempe. Keywords: analytical hierarchy process (AHP), rumah kedelai grobogan (RKG), the miles and snow typology